Removing the walls and textbook from the classroom: A case study of one creative entrepreneurship class of multinational students in South Korea - Parry, Z.; Baird, Craig (Queensland University of Technology, 2012)
Introducing creative elements into the syllabus and pedagogy of an Entrepreneurship class in a business school can be a risky endeavour for an educator and students alike. Populating the class with students from traditionally risk-averse cultures provides opportunities for everyone involved. Identifying the core behavioural issues for students in this learning experience brought creativity and entrepreneurship together in the academic environment. Emergent was a joint learning workshop using Skype, involving a book author, a multilingual multicultural class in South Korea and a culturally homogenous class in Indonesia. Along the way, the walls of the classroom were removed and the covers from the book disappeared. At the end of the journey, a new paradigm had emerged, driven and defined by the students that want to be the Entrepreneurs of their own worlds. This is the story of one creative entrepreneurship class of multinational students in South Korea.